Chromosome‐scale genome assembly of Poa trivialis and population genomics reveal widespread gene flow in a cool‐season grass seed production system - Caio A. C. G. Brunharo; Christopher W. Benson; David R. Huff; Jesse R. Lasky (Plant Direct)
Abstract Poa trivialis (L.) is a cool‐season grass species found in various environments worldwide. In addition to being a desired turfgrass species, it is a common weed of agricultural systems and natural areas. As a weed, it is an important contaminant of commercial cool‐season grass seed lots, resulting in widespread gene flow facilitated by human activities and causing significant economic losses to farmers. To better understand and manage infestations, we assembled and annotated a haploid genome of P. trivialis and studied troublesome field populations from Oregon, the largest cool‐season grass seed producing region in the United States. The genome assembly resulted in 1.35 Gb of DNA sequence distributed among seven chromosome‐scale scaffolds, revealing a high content of transposable elements, conserved synteny with Poa annua, and a close relationship with other C3 grasses. A reduced‐representation sequencing analysis of field populations revealed limited genetic diversity and suggested potential gene flow and human‐assisted dispersal in the region. The genetic resources and insights into P. trivialis provided by this study will improve weed management strategies and enable the development of molecular detection tests for contaminated seed lots to limit seed‐mediated gene flow. These resources should also be beneficial for turfgrass breeders seeking to improve desirable traits of commercial P. trivialis varieties and help to guide breeding efforts in other crops to enhance the resiliency of agricultural ecosystems under climate change. Significance Statement: The chromosome‐scale assembly of Poa trivialis and population genomic analyses provide crucial insights into the gene flow of weedy populations in agricultural systems and contribute a valuable genomic resource for the plant science community.